A study of fetomaternal outcome in cases of severe anemia in labor at a tertiary care center - Anadkat, Megh M.; Goswami, Kamal D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: In India, the prevalence of anemia is high because of fewer intakes of iron, folic acid and food sources that prevent iron absorption, coupled with poor bioavailability of iron is the major factor responsible for prevalence of anemia. More than iron deficiency, zinc, vitamin B12 and folate deficiency was highly prevalent due to ascariasis infestation. Methods: This study was carried out in the department of obstetrics and gynaecology at PDU medical college and hospital Rajkot, Gujarat from May 2021 to April 2022. Results: The study was conducted on 83 cases, the prevalence rate of severe anemia in the study population of PDU Medical College Rajkot was found to be 1.6% during this study period. 57.83% of cases delivered before term. Most of the patients 85.54% in the study group suffered from iron deficiency anemia. Most of the patients 49.40% were managed by transfusion of 2-pint PCV. Most common complications associated with anemia in pregnancy are atonic PPH, pulmonary oedema and surgical site infections in this study. A 67.46% of new-borns were of <2.5kg birthweight. High number of new-borns 39.75% with moderately abnormal APGAR scores were delivered. In this study, 75 patients were delivered vaginally, 5 instrumental deliveries were conducted to cut short the second stage of labor, 3 patients underwent LSCS due to major degree placentae previa and foetal distress. Conclusions: Severe anemia during labor affect the maternal and foetal outcome to a large extent. The major step in improving these outcomes is prevention of anemia which could be done at pre-pregnancy stages of a woman’s life, measures such as food fortification, deworming, mass haemoglobin screening among adolescent girls helps in this cause.